2017
DOI: 10.1007/s00125-017-4233-3
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive deficits associated with impaired awareness of hypoglycaemia in type 1 diabetes

Abstract: Aims/hypothesisThe aim of this study was to compare cognitive function in adults with type 1 diabetes who have impaired awareness of hypoglycaemia with those who have normal awareness of hypoglycaemia. A putative association was sought between cognitive test scores and a history of severe hypoglycaemia.MethodsA total of 68 adults with type 1 diabetes were included: 33 had impaired and 35 had normal awareness of hypoglycaemia, as confirmed by formal testing. The groups were matched for age, sex and diabetes dur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0
2

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(25 citation statements)
references
References 46 publications
0
23
0
2
Order By: Relevance
“…These recurrent episodes appear to lead to impairment in tracking and rectifying dysglycemia, thereby further impairing neural mechanisms in the process. Previous studies examining cognitive deficits and type 1 diabetes have identified a self‐perpetuating loop of disease mismanagement and increased cognitive decline (Grober et al, ; Hansen et al, ), which may at least partially explain the relationship between attention‐related neural dysfunction and disease duration apparent in the current study. With this progressive inability to manage the condition (i.e., maintain normoglycemia) leading to more rapid cognitive dysfunction, it is imperative that patients manage their glycemic levels carefully from the point of diagnosis to prevent detrimental long‐term outcomes.…”
Section: Discussionmentioning
confidence: 62%
See 2 more Smart Citations
“…These recurrent episodes appear to lead to impairment in tracking and rectifying dysglycemia, thereby further impairing neural mechanisms in the process. Previous studies examining cognitive deficits and type 1 diabetes have identified a self‐perpetuating loop of disease mismanagement and increased cognitive decline (Grober et al, ; Hansen et al, ), which may at least partially explain the relationship between attention‐related neural dysfunction and disease duration apparent in the current study. With this progressive inability to manage the condition (i.e., maintain normoglycemia) leading to more rapid cognitive dysfunction, it is imperative that patients manage their glycemic levels carefully from the point of diagnosis to prevent detrimental long‐term outcomes.…”
Section: Discussionmentioning
confidence: 62%
“…Considering the body of literature examining cognitive impairment in patients with type 1 diabetes, deficits in attentional processes may have a unique impact on daily care behaviors and long‐term disease management. The impact of chronic hypoglycemia in insulin‐treated type 1 diabetes is well‐known throughout the literature (Cryer, , ; Grober et al, ; Hansen et al, ; Rooijackers et al, ; Seaquist et al, ), with these patients experiencing two hypoglycemic episodes on average weekly and an annual incidence of severe hypoglycemia requiring third‐party intervention of 1.0 to 1.7 episodes per patient (Frier, ; McCrimmon & Sherwin, ). These recurrent episodes appear to lead to impairment in tracking and rectifying dysglycemia, thereby further impairing neural mechanisms in the process.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Unawareness of hypoglycemia, another long-term factor, has also been shown to induce further cognitive impairment. This hypothesis posits that as cognitive deficits arise, they affect the patient's ability to control glycemic levels, altering the awareness of the glycemic state and leaving the dysglycemia untreated, which ultimately leads to further cognitive decline (38,39). This cyclical decline increases the likelihood of devastating cognitive outcomes, such as mild Figure 5-Time series of parieto-occipital differences during maintenance.…”
Section: Discussionmentioning
confidence: 99%
“…Данная взаимосвязь может определяться гипогликемией -общим фактором риска этих состояний. У пациентов с НРГ выявлено снижение способности к запоминанию и распознаванию образов [41]. Данные мозговые функции в значительной степени зависят от гиппокампа -структуры, очень чувствительной к нейрогликопении.…”
Section: когнитивная дисфункцияunclassified